1979
DOI: 10.1007/bf00344961
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of n-species competition

Abstract: A measure of net interspecific competition is proposed which incorporates both direct and indirect effects between each species pair in a community. Indirect effects of one species on another may be mediated through other species in the community such that changes in the first species induce changes in other species which in turn directly affect the second species. Even in a competitive community these indirect effects are not necessarily always of a competitive nature and may sometimes actually act to oppose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 16 publications
0
86
0
Order By: Relevance
“…Neil1 (1984) showed that D. rosea can depress rotifer abundance through competition for phytoplankton in an oligotrophic lake. The outcome of interactions between two species may depend on the background community and the particular resource base present (Neil1 1975;Levine 1976;Lynch 1978;Lawlor 1979). Significant effects on Larimore Pond rotifers may not have been detected because the rotifers were rare during the period when D. pulex was abundant: the detection of such differences is easier when populations are large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neil1 (1984) showed that D. rosea can depress rotifer abundance through competition for phytoplankton in an oligotrophic lake. The outcome of interactions between two species may depend on the background community and the particular resource base present (Neil1 1975;Levine 1976;Lynch 1978;Lawlor 1979). Significant effects on Larimore Pond rotifers may not have been detected because the rotifers were rare during the period when D. pulex was abundant: the detection of such differences is easier when populations are large.…”
Section: Discussionmentioning
confidence: 99%
“…While useful in assessing interactions among particular species, small-scale experiments do not address the potential effects of a large species invading an entire community of small species, as would be the case if, for example, planktivorous fish were reduced in abun-Vanni dance in a lake. Since the outcome of competition between two species may depend on the presence of other "background" species (Neil1 1975;Lawlor 1979), the impact of a large species on particular small species may be different when an entire community is present than when only a few species are present. In large enclosures containing intact communities, large Daphnia spp.…”
mentioning
confidence: 99%
“…Since lower resource levels inhibit successful invasion, it remains that diverse communities should be more resistant (Tilman 1999). While interesting, this perspective is largely considered from a negative interaction perspective, and others (e.g., Lawlor 1979;Levine and Antonio 1999) have pointed out that species interactions that include facilitative effects can alter this result in such a way that increased diversity can actually decrease invasion resistance.…”
Section: Invasion and Ecological Stabilitymentioning
confidence: 99%
“…Recently, much attention has been given to indirect effects in ecosystem processes [for instance, see Lawlor (1979), Strauss (1991), Billick and Case (1994), Menge (1995), Abrams and others (1996), and Rosemond (1996)]. For example, Menge (1995) identified 83 subtypes of indirect effects in a rocky intertidal community and found that they accounted for about 40% of the change in community structure.…”
Section: Indirect Effectsmentioning
confidence: 99%